(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Indonesia and most developing countries (DGCs) are very enthusiastic to be part of the World Trade Organization (WTO) in a hope that free and fair trade could materialize and bring an improvement to their economies in the near future. Recognizing the fragile of their agricultural sectors and general economies, the WTO actually confers some provisions to DGCs in their transition to more open economies. But until the time of the Special Safeguard Mechanism (SSM) and Special Product (SP) introduction in July 2004, these provisions are hardly used by the DGCs for many reasons, which further provoke the DGCs to call for the SSM and SP provisions. As the SSM and SP facilities are already in existence, Indonesia and the G-33 should not leave these facilities as blank cheque that only to be written by ineligible party. They have to be active to formulate modalities and rules for the SSM implementation.